The pinch effect in microwave resonant streamer discharge - Esakov, I.I.; Grachev, L.P.; Khodataev, K. V. (Вопросы атомной науки и техники, 2000)
The work is devoted to experimental and theoretic study of a streamer discharge in the focus of microwave radiation in the open resonator. The observations show that if a gas pressure more than 0.1 atmosphere the single streamer discharge appears in the focus. When the resonant length of the streamer is achieved, the all energy storage of resonator is adsorbed by the streamer with very high efficiency. The simulations show that if gas pressure is quite enough the pinch force of the current inducted in the resonant streamer compresses the discharge plasma. One can hop that the forecasted high plasma parameters can be achieved and be applied not only for design of a gamma or neutron sources but for creation of a fusion reactor